(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Under the Pre GST regime, central and state government have levied multiple taxes on the samesupply chain. There was cascading effect of taxes, as taxes levied by the central government, were notallowed as set off against the taxes levied by state government. In the view of the above difficulties, thecertain taxes have been subsumed in a one tax called the goods and service tax (GST). Automobileindustry in India is one among the most victorious and rising manufacturing industry after liberalization.The industry has prospective to grow and become a most important contributor for the economicdevelopment and employment formation. The Indian government has also identified the need forAutomobile industry in the Indian economy and is currently functioning on Automotive Mission Plan 2026.The automobile industry produces commercial vehicles, passenger‘s cars, and three and two-wheeler.Bythe outline of GST, where all the taxes are subsumed into one, it becomes necessary to foresee theimpact of GST on this industry. This paper covers the overall impact of GST on Automobile sector inIndia.